How many crashes are caused by driver interaction with passengers? A meta-analysis approach. (June 2018) - Theofilatos, Athanasios; Ziakopoulos, Apostolos; Papadimitriou, Eleonora; Yannis, George
Abstract: Introduction: Conversation and other interactions with passengers while driving induce a level of distraction to the person driving. Method: This paper conducts a qualitative literature review on the effect of passenger interaction on road safety and then extends it by using meta-analysis techniques. Results: The literature review indicates that the distraction due to passengers is a very frequent risk factor, with detrimental effects to various driving behavior and safety measures (e.g., slower reaction times to events, increased severity of injuries in crashes), associated with non-negligible proportions of crashes. Particular issues concern the effect of passenger age (children, teenagers) on which the literature is inconclusive. Existing studies vary considerably in terms of study methods and outcome measures. Nevertheless, a meta-analysis could be carried out regarding the proportion of crashes caused by this distraction factor. The selection of studies for the meta-analysis was based on a rigorous method including specific study selection criteria. The findings of the random-effects meta-analyses that were carried out showed that driver interaction with passengers causes a non-negligible proportion of road crashes, namely 3.55% of crashes regardless of the age of the passengers and 3.85% when child and teen passengers are excluded. Both meta-estimates were statistically significant, revealing the need for further research, especially considering the role of passenger age. Practical applications: Stakeholders could make good estimates on future crash numbers and causes and take action in order to counter the effects of passenger interaction. Highlights: This paper conducts a review on the effect of passenger interaction on crashes. Afterwards meta-analysis techniques are conducted. 3.55% of crashes are caused by passenger interaction for all age groups. The respective proportion is 3.85% when child and teen passengers are excluded.